(untitled) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the history of Viysko Zaporozke Nyzove (Lower Zaporizhzhyan Host) in the difficult period of the end of XVII – beginning of XVIIIth century. Basing upon the new archive sources, the author proves the conclusion that during 1720-1730-ies anti-Tatar and anti-Turkish opinions from times to times grew stronger in the midst of Zaporizhzhyan commumity, resulting in final decision to turn back under the Russian protectorate.